Building strong partnerships: Understanding the mechanisms by which quality coach-athlete relationships affect objective performance in professional cricket - Phillips, K.; Jowett, S.; Krukowska-Burke, A.; Rhind, D. J. (International Journal of Sports Science & Coaching, 2025)
The purpose of the study was to explore possible explanations for the link between the quality of a coach-athlete relationship (CAR) and performance in professional cricket. Understanding the mechanisms through which CARs influence on-field performance may provide practical insights for sport practitioners including coaches. A total of 54 (28 male and 26 female) professional cricketers from the United Kingdom completed a survey measuring CAR quality, communication strategies, psychological safety, and collective efficacy, along with performance data from 50,159 deliveries across the 2023 county championship and Rachel-Heyhoe Flint trophy. Bootstrap analysis of the main variables of the study revealed that CAR quality positively predicted skill execution performance in bowlers (line and length target area %). Parallel mediation models also found that communication strategies (i.e., conflict management and openness), psychological safety, and collective efficacy explained the association between CAR and cricket performance. This research explains the link between CAR and on-field objective performance, suggesting potential reasons for performance success and failure. It paves the way for additional research that aims to explain the impact of social-environmental and interpersonal factors on objective performance.